THE CONTRIBUTION OF SYEKH ABDUL KARIM AMRULLAH’ S THOUGHTS IN ISLAMIC EDUCATION AND ITS RELEVANCE TO CURRENT ISSUES - Fatmawati Fatmawati (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2017)
This paper aims at describing the educational system established by Sheikh Abdul Karim Amrullah and its relevance in the present day. This is a library research using a biographical research method. Sources of data are documents related to the roles of Sheikh Abdul Karim Amrullah in Islamic education. In addition, the researcher also conducted interviews and observation in Madrasah Thawalib Padang Panjang. The result shows that the Madrasah still maintains the main purpose of education proposed by Sheikh Abdul Karim Amrullah as the founding father. Moreover the Madrasah, beside implementing the old curriculum, has adjusted to the national education standard by incorporating general learning materials in today’s teaching.